'Battery hens' or 'nuggets of gold': a qualitative study on the barriers and enablers for altruistic egg donation. (8th August 2022) - Hogan, Rosemarie G.; Hammarberg, Karin; Wang, Alex Y.; Sullivan, Elizabeth A.
Abstract: The demand for donated eggs outstrips supply in countries such as Australia where only altruistic egg donation is permitted. We conducted semi-structured interviews with women ( n = 18), who had donated eggs in Australia in the last three years, to identify barriers and enablers for altruistic egg donation. Women reported difficulties in accessing trusted information on all aspects of egg donation and limited public awareness about the need for donor eggs. They generally had a good experience of pre-donation counselling and of the care provided by the fertility clinic staff. However, post-donation follow-up was deemed inadequate. Participants offered suggestions for how public education campaigns could enhance awareness about egg donation and how clinics could improve the post-donation experience. The findings indicate that the availability of independent, easily accessible, evidence-based information on egg donation; improved public awareness about the need for donor eggs; and proactive recruitment of donors may increase the local supply of donor eggs. Better clinic follow-up care, including post-donation counselling, would improve donors' experience of altruistic egg donation.